Prenatal diagnosis of middle interhemispheric variant of holoprosencephaly: Report of two cases. Issue 7 (8th February 2021) - Zantow, Emily; Bryant, Stefanie; Pierce, Stephanie L; DuBois, Molly; Maxted, Marta; Porter, Blake
Abstract: Holoprosencephaly ranges in severity based on the degree of anatomic abnormality. Middle interhemispheric variant of holoprosencephaly is a less common and often milder variant that has the characteristic sonographic findings of an absent cavum septum pellucidum and a single fused ventricle. This subtype may be associated with genetic conditions that have not been well‐described in the literature. We present two cases of middle interhemispheric variant of holoprosencephaly diagnosed on fetal ultrasound.